Karyological Examination of Ornithogalum orthophyllum Ten. and Ornithogalum oligophyllum E. D. Clarke - Kıran, Yaşar; Öğer, Sibel; Doğan, Gülden (Uğur ÇAKILCIOĞLU, 2024)
In this study, two species of Ornithogalum L. genus (Ornithogalum orthophyllum Ten. and Ornithogalum oligophyllum E. D. Clarke), one of the important genus of the Asparagaceae family, were examined in terms of karyological aspects. The plant materials used in the study were collected from the natural distribution areas of the plants around Elazığ 2019. Some of the collected samples were turned into herbarium samples and stocked in the FU herbarium. Bulbs obtained from the collected samples were used in cytotaxonomic studies. As a result of the studies carried out in dividing somatic cells, chromosome counts and karyotype analyzes of the species were made and their ideograms were drawn. Chromosome number were determined as 2n=20 and karyotype formula M+3m+3sm+3st in Ornithogalum oligophyllum, Ornithogalum orthophyllum species as 2n=14 and karyotype formula as 3m+2sm+2st.
Keywords: Botany (Other); Bitki Bilimi (Diğer)